Multicomponent Reactions in the Synthesis of γ-Lactams - Martinez de Marigorta, Edorta; de los Santos, Jesús M.; Ochoa de Retana, Ana M.; Vicario, Javier; Palacios, Francisco (Synthesis, 2018)
This review summarizes the synthesis of γ-lactam ring using multicomponent reactions.1 Introduction2 Pyrrolidin-2-ones3 Pyrrolin-2-ones (Dihydro-2H-pyrrol-2-ones)4 Final Remarks
Keywords: multicomponent reactions; γ-lactams; pyrrolidin-2-ones; pyrrolin-2-ones; dihydro-2H-pyrrol-2-ones